Direct effect of basic fibroblast growth factor on gene transcription in a cell-free system. - Nakanishi, Y (1992)
Recent findings on the translocation of intact fibroblast growth factor (FGF) into the cell nucleus suggest that it functions directly in nuclear events. We examined the effect of human basic FGF (bFGF) on gene transcription in a cell-free system. When mouse genes encoding phosphoglycerate kinases 1 and 2 (Pgk-1 and Pgk-2) were transcribed by using nuclear extracts of Ehrlich ascites tumor cells, FGF affected transcription in different ways: in the presence of bFGF, transcription of the Pgk-1 gene was inhibited, whereas that of the Pgk-2 gene was enhanced. When viral genes were tested, transcription of the adenovirus major late DNA was slightly stimulated but that of the adenovirus early E1A DNA or the human immunodeficiency virus DNA was not changed by the addition of bFGF. Moreover, the presence of a distinct 5' upstream region of the Pgk-2 gene, which includes a negative cis-acting element, was required for transcription stimulation by bFGF. These results suggest that bFGF can regulate transcription directly in the nucleus in a gene-specific manner.